डॉ. अंबेडकर का आधुनिक भारत में "नव बौद्ध यान धर्म" के रूप में पुनरुत्थान। (Bodhi Path, 2025)
Dr. B.R. Ambedkar, during the mid-20th century, spearheaded revolutionary changes in modern India against the caste system, casteism, racism, religious rituals, Brahmanical dominance, communalism, and untouchability. His efforts led to the welfare of marginalized communities, including the Shudras, Dalits, oppressed classes, indigenous people, and the socially backward. He inspired society to work towards freedom, equality, and fraternity.Ultimately, on October 14, 1956, Dr. Ambedkar renounced Hinduism and, along with his followers, embraced Buddhism. He established Neo-Buddhism, a modern adaptation of Buddhist philosophy.This research paper aims to examine the ideas of Buddha's Buddhist philosophy and Ambedkar's Neo-Buddhist movement, focusing on their contributions to social reform and the structural transformation of society.
Keywords: Dr. B.R. Ambedkar; caste system